Intratracheal Administration of Nanoplastics With Varying Surface Hydrophobicity Results in Coarsely Vacuolated Alveolar Macrophages, Transient Respiratory Inflammation, and Mild Collagen Deposition - Anna Babin Morgan; Yanira Riffo‐Vasquez; Aateka Bodhaniya; Stuart A. Jones; Ben Forbes; Kavitha Sunassee; Rafael T. M. deRosales; Stephanie Wright; Clive Page; Lea Ann Dailey (Nano Select)
ABSTRACT Inhalation of biopersistent nanoplastics may have adverse effects on lung health. By varying the acetate content of poly(vinyl acetate‐co‐alcohol) (PVAc), model nanoplastics with different surface hydrophobicity can be produced to study the effects of nanoplastic hydrophobicity in the lung. PVAc nanoplastics with a high hydrophobicity, administered by oropharyngeal aspiration to C57BL/6j mice (300 µg; ∼10 mg/kg), show transient pulmonary inflammation which peaks at 24 h post‐administration and resolves by day 7. Hydrophilic PVAc induces no inflammatory effects at the same dose. Pulmonary administration of hydrophilic and hydrophobic PVAc nanoplastics increases the prevalence (∼30%–35%) of distinctive coarsely vacuolated alveolar macrophages over 28 days. Hydrophobic PVAc and silica nanoparticles (control) induce minor increases in collagen deposition, but do not stimulate tissue remodeling to the same extent as a bleomycin model of fibrosis. Longitudinal micro‐CT imaging is explored as a non‐invasive methodology for detection of lung fibrosis. A bespoke image analysis method to quantify high density tissue signal volume correlates moderately well with histopathology‐derived collagen deposition data (R2 = 0.73). In summary, inhaled nanoplastics with high surface hydrophobicity induce transient inflammation following a single administration of 300 µg, an increase in coarsely vacuolated macrophages and mild increases in collagen deposition.